The relationship between an electronic mental health stigma campaign and suicidal thoughts and behaviours: a two-arm randomized controlled trial in the Australian construction industry. (12th May 2019) - Milner, A; Aitken, Z; Law, P C F; LaMontagne, A D; Mann, C; Cooper, T; Witt, K
Abstract: Males employed in the construction industry are at greater risk of suicide than other employed males. It is plausible that a high level of stigma against mental health problems explains the elevated rates of suicide among this group. This study sought to test the effectiveness of an electronic mental health stigma intervention on suicide ideation, communication about suicide and attempts. Participants were randomly assigned to receive either a series of brief contact interventions over a 6-week period or a wait list control. Suicidal ideation, communication about suicide and suicide attempts were assessed using the Suicidal Behaviors Questionnaire-Revised at post-intervention. We used linear regression to assess effectiveness at post-intervention, adjusting for relevant covariates using both conventional methods and a propensity score approach. Results indicate that the intervention had no significant impact on suicidal thoughts, communication or suicide attempts. There was some indication that individuals in the intervention group reported a slight increase in attempts and communication about suicide. These observations underscore an urgent need for more research to understand the complex and nuanced relationship between stigma and suicide in non-clinical populations.